NOP10 predicts lung cancer prognosis and its associated small nucleolar RNAs drive proliferation and migration - Cui, Chunhong; Liu, Yi; Gerloff, Dennis; Rohde, Christian; Pauli, Cornelius; Köhn, Marcel; Misiak, Danny; Oellerich, Thomas; Schwartz, Schraga; Schmidt, Lars Henning; Wiewrodt, Rainer Gerhard; Marra, Alessandro; et al. (Oncogene, 2021)
Prognostic markers, Non-small-cell lung cancer